The modern Malay : A comparative study of Katherine Sim’s Malacca Boy (1957) and Mahathir Mohamad’s The Malay Dilemma (1970) - Mohamad Rashidi Mohd Pakri,; Grace, V.S. Chin; Afzal, Malik Haroon (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines the representations of the modern Malay in Katherine Sim’s Malacca Boy (1957), which is set against the backdrop of historical events in British Malaya, including the Japanese Occupation. An important historical commentary on Malay life and modernising Malaya, the novel invites us to revisit the ingrained scholarly views about colonial writers as well as the contemporary racial discourse about the Malay. Using a new historicist approach, this article has a two-fold aim: first, to analyse how Malacca Boy engages the critical issues of race and modernity in its portrayal of Malay identity through the protagonist, Hassan; and second, to examine the relevance of Sim’s portrayal in relation to the contemporary political narrative of the Malay in Mahathir Mohamad’s The Malay Dilemma (1970). Indeed, very little research has been done to consider how the trajectories of fiction and non-fiction intersect in the discussion of race and modernity, and therein lies the novelty and strength of our study. Although it is uncommon to compare literary fiction and non-fiction writing, we contend that such an unconventional approach to literary analysis will yield important insights to the narration of Malaysian history, both in the colonial past and postcolonial present, and the place of the modern Malay in it.